(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2021)
Existential thinking tells us that we are not fixed selves – we are who we are in relation to our context and to others. We also believe that our past does not cause us to be who we are. It is our unique response to our past that we carry with us in the present. How we are in the present plays a part in how we remember our past. In other words, our present co-creates our past. But does our past also co-create our present? How do I reconcile my experience that part of me remains fixed and unchanging while change is happening to me and my world all the time? Can we ever understand ourselves in the present without understanding our past selves? I believe that we can’t, and yet this dimension has been somewhat neglected on the therapy training courses I have been on. I hope to show how my attitude to life is graphically expressed in my past lives and constantly being played out in the present on many levels while my so-called ‘inner fixed self’ acts as my loyal connection throughout my life.